English Literacy untuk Meningkatkan Pemahaman Bahasa Inggris Anak-Anak Panti Asuhan Assyaamil - Juniani, Juniani; Hartono, Hartono; Willestania, Michelle; Prawira, Edwin; Loi, Leonard; Youpi, Youpi; Hudori, Mahfuz (National Conference for Community Service Project (NaCosPro), 2019)
The purpose of this project is to increase knowledge about English and Online shop and to help them increase their income by selling products in the online shop. The implemented method of this project is to teach both English and how to sell products in the online shop to the orphans in Nongsa. The teaching methods are by oral explanation and playing games. Learning English with an oral explanation which was continued with a game about the material that has studied and Learning Online shop with an oral explanation. The result of this project is learning English by playing games is easier to understand than learning English with oral explanation and learning English will be more fun by playing games.